Wave modelling for the German Bight coastal-ocean predicting system. (August 2015) - Staneva, J; Behrens, A; Wahle, K
Abstract: Ocean wave modeling has shown impressive developments, both in theoretical aspects as in the quality of the results available to users. The recent advances in development of the WAM wave model for forecasts applications at operational services and climate assessments for the North Sea and the German Bight are presented here. Ocean waves control the exchange of energy, momentum, heat, moisture, gas, etc. between the ocean and the atmosphere in the earth system. The impact of waves on currents and water levels in coastal areas is demonstrated. This is an important step towards a fully coupled atmosphere-wave- ocean modelling system. The synergy between wave observations and models for the North Sea and German Bight is increased on the road to improving the ocean state estimate and predictions in the coastal areas and generating up-to-date information, products and knowledge.